An Event Study on the Indonesian Ulema Council's Fatwa Regarding the Boycott of Israel and United States Affiliated Companies in Indonesia - Salman Al farisi; Novi Puspitasari; Agus Mahardiyanto (KEDJATI Foundation, 2025)
This research aims to evaluate abnormal returns surrounding the announcement of the Indonesian Ulema Council’s (MUI) Fatwa Number 83 of 2023 and to compare abnormal returns before and after the announcement. This study employed an event study approach. The population consists of companies listed on the Indonesia Stock Exchange (IDX). The research sample included nine companies affiliated with Israel and the United States, as well as nine non-affiliated companies from the same industry sectors to provide a balanced comparison. Abnormal returns were calculated using the single index model. The independent variable in this study was the return of the Composite Stock Price Index (IHSG), while the dependent variable was the stock return. The results indicated that there were no significant abnormal returns surrounding the announcement of MUI’s Fatwa Number 83 of 2023 for either affiliated or non-affiliated companies. Furthermore, the findings revealed no significant differences in abnormal returns before and after the announcement for either group of companies.